EDUKASI KOMPRES BAWANG MERAH DALAM PENANGANAN DEMAM ANAK DENGAN PENDEKATAN TEORI HEALTH BELIEF MODEL - Amal, Andi adriana (Journal of Community Engagement in Nursing, 2024)
Fever is the body's response that most often occurs due to both infectious and non-infectious diseases. Children are a group vulnerable to fever because their immune system is still not optimal. According to the World Health Organization (WHO), in 2020, the number of fever cases worldwide reached 11-20 million people and it is estimated that between 128,000-161,000 people die every year. Therefore, it is important to provide education on how to treat fever, one of which is using onion compresses. Community Service aims to increase public knowledge about treating fever in children using shallot compresses. The approach used by the health belief model theory shows that there are differences in knowledge before and after being given health education. Good knowledge will be the first step that people can take in dealing with children's fevers so that they avoid danger. Education using the health belief model theory approach can be used to increase public knowledge. Keyword: children, compresses, , fever, health belief mode, union